In Vivo Evidences of Nanosecond Pulsed Electric Fields for Melanoma Malignancy Treatment on Tumor-Bearing BALB/c Nude Mice. (August 2014) - Guo, Fei; Yao, Chenguo; Li, Chengxiang; Mi, Yan; Peng, Qiao; Tang, Junying
In order to get in vivo evidences of nanosecond pulsed electric fields (nsPEF) for skin tumor treatment, tumor models in 10 female BALB/c nude mice were established by inoculating them with human melanoma cells A375. These mice were randomly divided into treated group (exposed to nsPEF with intensity of 20 kV/cm and duration of 300 ns) and control group equally. Five days post-nsPEF treatment, tumor growth in the treated group was effectively inhibited ( P < 0.01 compared with that in control group), typical apoptotic characteristics (DNA damage and fragmentation) were observed by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), and significant increases in Bax and decreases in Bcl-2, micro-vessel density (MVD), vascular endothelial growth factor (VEGF) and proliferating cell nuclear antigen (PCNA) were observed by immunohistochemistry ( P < 0.01). These experimental results indicate that in vivo tumor growth can be effectively inhibited by nsPEF, which activate two targets, apoptosis initiation and angiogenesis inhibition.